Lucid Dreams And Out-Of-Body Experiences Reports: Differences In Emotional Content, Dream Awareness, And Dream Control - Gallo, Francisco Tomás (2023)
Lucid dreams (LDs) and out-of-body experiences (OBEs) are phenomena characterized by the return of higher cognitive abilities during sleep, including reflective self-awareness and abstract thought. Given the similarities in reflective self-awareness between LDs and OBEs, some authors consider them variations of the same phenomenon. This study aimed to compare the differences in content between non-LDs, LDs, and OBEs obtained from 60 participants over a two-month period, with 916 dream reports collected. The dream reports were analyzed using automatic methods based on Lexicons such as NRC Emotion Lexicon and Empath, and were scored based on Hall and Van de Castle´s dream content scoring system with variations and additional measures. Results showed that OBE dreams were characterized by higher occurrences of negative emotions compared to both lucid and non-lucid dreams as measured by automatic and manual scoring systems. Also, more OBE dream reports contained words related to agency and insight, higher manual scoring of dream control-related expressions, and more total sensations, dream activities, reference to prospective memory evocations, spatial and body references, and more difficulties with movement within the dream environment, than lucid dreams. The findings support the idea that OBEs represent unique experiences distinguished from lucid dreams.